KEANEKARAGAMAN DAN KEMELIMPAHAN LARVA INSEKTA AKUATIK SEBAGAI BIOINDIKATOR KUALITAS AIR DI SUNGAI GARANG, SEMARANG - Sitta Maulina Marpaung; Fuad Muhammad; Jafron Wasiq Hidayat (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2014)
River is a natural habitat of macrobentik organism which is include the larvae of aquatic insects. The larvae of aquatic insects can be used as bioindicators of water pollution because they are can accomodate the change of the environmental. The purpose of this research is determine the community structure of aquatic insect larvae as well as its aspect bioindicators. This research used survey method and sampling techniques by purposive sampling. Location of the research consisted of four stations determined based on area’s function along the Garang River. At each station represent by three samples taken with surber mesh size 25 x 40 cm. The result this research showed that the larvae of insects were found in every observation station which is consists 15 genera, i.e namely Heptagenia, Stenacron, Baetis, Cloeon, Procleon, Caenis, Glossosoma, Hydropsyche, Cheumatopsyche, Chimarra, Tinodes, Chironomus, Chrysop, Isoperla and one of the family Culicidae was unidentified. The highest diversity found at Gebugan village ) in the rice fields (the diversity value of 2.17. The lower diversity at Tinjomoyo street with only reached diversity make 1,45. The conclusions of this study grouped Garang River that be into two categories, they are moderately polluted and contaminated. Heptagenia and Baetis categorized as positive bioindicator forests, fields and settlements, where as negative bioindicator industrial area are Procleon and Glossosoma. Keywords : Aquatic insect larvae , Garang River , Bioindicator